Initial Exploration of the In Vitro Activation of GLP-1 and GIP Receptors and Pancreatic Islet Cell Protection by Salmon-Derived Bioactive Peptides - Crawford Currie; Christian Bjerknes; Bomi Framroze (Marine Drugs)
This study examines the in vitro effects of a soluble protein hydrolysate (SPH) derived from Atlantic salmon (Salmo salar) on incretin receptor activity and pancreatic islet cell protection to explore the mechanisms underlying SPH’s observed benefits on weight loss and metabolic health in overweight individuals. SPH demonstrated a dose-dependent enhancement of glucagon-like peptide-1 (GLP-1) and gastric inhibitory polypeptide (GIP) receptor activity, with significant increases of 2.4-fold (p < 0.05) and 2.6-fold (p < 0.01) at 10 mg/mL, respectively, compared to the control. Pancreatic islet cell assays showed a substantial proliferation effect, with up to a 57% increase at 50 µL/well, indicating potential protective properties against inflammation-induced cell loss. Notably, the smallest SPH peptide fraction (<1000 Da) exhibited GLP-1 agonist activity comparable to semaglutide, a widely used therapeutic agent, underscoring SPH’s potential efficacy in modulating metabolic pathways. These results suggest that SPH not only enhances key incretin signaling but also promotes islet cell health, positioning it as a promising dietary intervention to improve age-related metabolic health, including the weight gain and underlying adverse metabolic changes frequently encountered through the menopause.